Draft Genome Sequence of Diplodia seriata F98.1, a Fungal Species Involved in Grapevine Trunk Diseases - Robert-Siegwald, Guillaume (Genome Announc, 2017)
The ascomycete Diplodia seriata is a causal agent of grapevine trunk diseases. Here, we present the draft genome sequence of D. seriata isolate F98.1 (37.27 Mb, 512 contigs, 112 scaffolds, and 8,087 predicted protein-coding genes).